2008级(下)第16次è¯&frac34

2008级(下)第16次è¯&frac34

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: + * s + l < y L M n -1 B :~ * f M = s. M 1 , M 2 , , M n - 1 si , o A ( i ,i ) M i M2 M i -1 M1 x ( i , i ) si , M i ( i , i ) si . M ( i , i ) si . i =1 n M = lim ( i , i ) si . 0 i =1 n 1. 2 x Lx xoyX x Lx x iX x x f ( i , i ) si , .x Lx .x p D i^* x , ,x f ( x, y) n M 1 , M 2 ,, M n-1x Lx si , x ( i , i )x y B L M n-1 ( i , i ) M i M2 M i -1 M1 f ( i , i ) si , i =1 n o A x 龪* 龪* x x x 龪* , 龪* L , x 0x , f ( x, y) x x x L f ( x , y )ds, n L f ( x , y )ds = lim f ( i , i ) si . 0 i =1 x 龪* M = ( x , y )ds . L 2. i 龪 2 f ( x , y ) i 龪* i 龪* 3. 2 L2 , . f ( x , y , z )i 龪* L f ( x , y )ds 2 i 龪 n 2 i 龪 f ( x , y , z )ds = lim f ( i , i , i ) si . 0 i =1 1. L( ) L1 , ( L = L1 + L2 ) L2 X龪* L1 + L2 f ( x , y )ds = f ( x , y )ds + f ( x , y )ds . 2. x f ( x , y )x LX龪 L f ( x , y )ds . 4. 2 (1) [ f ( x , y ) g ( x , y )]ds = f ( x , y )ds g ( x , y )ds . L L L ( 2) kf ( x , y )ds = k f ( x , y )ds ( k2 L L L L1 L2 ). ( 3) f ( x , y )ds = f ( x , y )ds + f ( x , y )ds . ( L = L1 + L2 ). x f ( x , y )x Lb a * , x = ( t ), L*b a ( t )x y = ( t ), ( t ), ( t )x [ , ] , x L f ( x , y )ds = f [ ( t ), ( t )] 2 ( t ) + 2 ( t )dt ( < ) : 1. 8 2. f ( x , y )2 x , y 8`s x (1) L : y = ( x ) a x b. b a 8 , 8`s * ; . L f ( x , y )ds = f [ x , ( x )] 1 + 2 ( x )dx . (a < b ) ( 2) L : x = ( y ) c y d. d L f ( x , y )ds = f [ ( y ), y ] 1 + 2 ( y )dy . c (c < d ) : : x = ( t ), y = ( t ), z = ( t ). ( t ) f ( x , y , z )ds = 2 ( t ) + 2 ( t ) + 2 ( t )dt f [ ( t ), ( t ), ( t )] ( < ) 1 2 I = xyds, L : 2 L x = a cos t , (2 2 y = b sin t , ). x I = a cos t b sin t ( - a sin t ) 2 + ( b cos t ) 2 dt = ab sin t cos t a 2 sin 2 t + b 2 cos 2 t dt a ab = 2 u2du ( 2 b a -b 2 0 2 0 u = a 2 sin 2 t + b 2 cos 2 t ) ab(a + ab + b ) = . 3(a + b ) 2 2 2 2 I = yds, L y2 = 4 x 2 x 3 L : y 2 = 4 x , 2 (1,2)2 (1,-2)2 2 . y 2 I = y 1 + ( ) dy = 0. -2 2 I = xyzds, : x = a cos , y = a sin , z = k x 2 . ( 0 2 ) I = a 2 cos sin k a 2 + k 2 d 0 1 2 2 2 = - ka a + k . 2 4 x I = x 2ds , x x x x , 2 x2 + y2 + z2 = a2 , x + y + z = 0. x 2ds = y 2ds = z 2ds . 1 2 I = ( x 2 + y 2 + z 2 )ds 3 a 2a 3 = ds = . ( 2a = ds, X龪* 3 3 2 ) (1) 2 ( x , y )2 L龪 = Lds ; L2 , , M = L ( x , y )ds ; ( 2) x f ( x , y ) 1x , Lx ( 3) 2 f ( x , y )2 2 Sx z = f ( x, y) s L ( x , y )2 L = f ( x , y )ds . ( 4) 2 2 x2 y8龪* 2 , I x = y ds , L I y = x ds . L ( 5) 8 龪* xds , x= ds L L yds . y= ds L L 1P 8 2P 8 3P 8 P146 2 9-1 1 2 2 2 3 2 4. 2 13s f * [end] ...
View Full Document

This note was uploaded on 03/01/2010 for the course ENGINEER 261 taught by Professor Liu during the Spring '10 term at South University Online.

Ask a homework question - tutors are online